Measurement of vibrational energy flow in a plate with high energy flow boundary crossing using electronic speckle pattern interferometry - Thomas Eck; Stephen Walsh (2012)
The measurement of vibrational energy flow is an important tool in understanding the vibrational behaviour of structures. In the past, because of transducer constraints, the measurement of vibrational energy flow was mostly restricted to single point measurements. However, recent developments in advanced laser measurement techniques, such as electronic speckle pattern interferometry (ESPI), have gained interest in applying two-dimensional, multi-point measurement techniques to the estimation of vibrational energy flow. This paper addresses the measurement of vibrational energy flow in a plate by using an ESPI based vibrational energy flow measurement technique. A radially symmetric bending wave plate vibration model is introduced and theoretical expressions for energy-based quantities are derived. To assess the accuracy of the measurement method, these theoretical quantities are compared to synthetic results derived from the ESPI energyflowmeasurement technique. The ESPI measurement technique is also applied to an experimental ‘infinite’ plate. Thus, a specially designed experimental apparatus was constructed so as to minimise undesired wave reflections in the plate and, thus, achieve a high energy flow boundary crossing at the edges of the plate. To reduce the effect of optical noise contamination on the ESPI measured out-of-plane plate displacement data, optimal filters were applied prior to the vibrational energy flow computation. To appraise the accuracy of the experimental method, measured vibrational power on the plate is compared with measured vibrational input power. A difference of less than 1 dB between both quantities indicates that vibrational energy flow within a rectangular plate that contains radially symmetric wave propagation can be measured to a good degree of accuracy if appropriate filtering is applied.